Dileme v zvezi z napotitvijo delavcev - Tičar, Luka (Podjetje in delo, 2017)
The field of posting of workers in the framework of the provision of services represents a serious problem for the EU. Despite a wish to guarantee workers proper labour protection, that is not case in practise. The situation has partially improved with the adoption of an implementing directive, which prevents abuse and circumvention, but the initial problem remains. According to valid legal regulation and case law of the EU Court, posted workers are entitled only to minimum labour rights of the host state. A revision of the basic directive is in the process of adoption, which would bring some changes in this regard. Slovenia transposed the implementing directive by enacting the Transnational Provision of Services Act. The content of the Employment Relationship Act is already comparable with the draft text of the revision of the basic directive.
Keywords: freedom of services; implementing directive; izvedbena direktiva; minimalni obseg pravic delavcev; minimum level of workers' rights; napoteni delavci; posted workers; svoboda izvajanja storitev